MANIFESTASI KEPERCAYAANNYA MASYARAKAT JEPANG TERHADAP DEWA EBISU - Heryana, Chrisna Yuda Tama; Ali, Mohammad (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2023)
Besides being famous for its technological advances, Japan is also famous as the land of gods because there are many mythologies about gods in Japan and one of the famous Gods is the God Ebisu. Ebisu is a god of Luck who is still believed to exist by the people of Japan. Based on the enthusiasm of the Japanese people towards the God Ebisu, the author wanted to conduct research with the aim to determine the manifestation of the belief of the Japanese people to the God Ebisu and the embodiment of the God Ebisu in Japanese pop culture. The method used by the author in this study is a qualitative method with a descriptive approach the results of this study is the discovery of some manifestations of the belief of the Japanese people to the God Ebisu that is praying,idols and Matsuri. The first manifestation is to pray to the God Ebisu, this is the most frequent manifestation of Japanese society because it is a manifestation that is considered the most practical. The second is an idol, the Japanese people believe in the blessing of the God Ebisu and his protection they can also get in the form of an object. The last is Matsuri, this Matsuri activity is essentially an activity to invite gods or welcome the presence of Gods, by presenting all the dishes that exist and by showing an attitude of devotion to the Gods in order to get guidance and blessings. The embodiment of the God Ebisu in Japanese popular culture is in the form of a character who has the basis of the God Ebisu. The depiction of Ebisu's form and nature in popular culture has undergone changes when compared to the form and nature of Japanese folk mythology. The existence of this change in depiction is also felt to function as a form of adaptation of the Times. Keywords: Beliefs, Japanese Society, Mythology, Ebisu